A first time lesson study that turned into a learning study. Issue 4 (3rd October 2019) - Klammer, Simone; Hanfstingl, Barbara
Abstract : Purpose: The purpose of this paper is to present an implemented lesson study (LS) in English as a second language course for 11-year-old students in the fifth grade. The aim of the research lesson was to learn how to describe a person systematically. Design/methodology/approach: Two LS cycles in two different classes were conducted and evaluated using systematic observation, case student interviews and student feedback. The data were analysed by the involved teacher team and the mentor. Findings: The study shows that and how LS and variation theory promotes theory-based lesson preparation and postprocessing as well as team orientation among teachers without LS experience. Second, the lesson data show how elements of variation theory lead to a significant improvement in student learning activity. Originality/value: This paper provides insights how teachers apply a first time LS and variation theory and how this effects student learning positively.